Effect of different bedding materials on the reproductive performance of broiler rabbits (Journal of Laboratory Animal Science, 2024)
The effect of different bedding materials on the performance was studied in eighteen adult female broiler rabbits in three  kindlings at Small Animal House, Veterinary College Bangalore. Based on bedding material, rabbits were divided into  coconut coir group (T1), ragi straw (T2) and wire mesh group without any bedding material (T3). Litter size and litter  weight at birth were6.22±0.37 and 246.30±10.74 in T1 group, 5.66±0.37 and 223.70±11.49 in T2 group and 5.77±0.27 and  224.80±8.242 in T3 group respectively. The average litter size and weight at weaning were 5.72±0.28 and 1488±38.73 in  T1 group, 4.94±0.26 and 1202±35.45 in T2 group and 4.50±0.27 and 991±39 in T3 group respectively. The highest litter  size and weight at weaning were recorded in T1 group which was significantly different (P
Keywords: Rabbit; litter size; litter weight; coconut coir; ragi straw; wire mesh